Analysis Of Consumer Perceived Value To Quality Service Healthcare During The COVID-19 Pandemic At Tanjung Balai City Hospital - Manurung, Charles; Eliza Putri Lubis, Yolanda; Kaban, Karmila (International Journal of Health and Pharmaceutical (IJHP), 2023)
Background:Perception is a person's process of knowing several things through his five senses. Perception does not appear to exist because it occurs outside of awareness, but perception depends on the complex functions of the nervous system. Health service facilities, during the COVID-19 period, became something terrible for the community, where people who were sick were afraid to come to health services because they were worried about being diagnosed positively with COVID-19, whether health services during COVID-19 increased or decreased. Objective: to analyze the quality of health services on public perception at Tanjung Balai General Hospital during the Covid-19 Pandemic. Method: This type of research is observational analytic research. The research location was at the Tanjung Balai General Hospital which was carried out in November 2022. Results: Most respondents were in the 45–54-year-old age category (32.2%). Based on gender, the most were women as many as 208 people (77%). Based on work, the most were in the PNS category, with 105 people (38.9%). Based on education at most S1 as many as 63 people (23.3%). Most people's perceptions of the quality of Tanjung Balai General Hospital were in the good category with 144 people (53.3%) and those who said they were not good were 126 people (46.7%). There is a significant relationship between people's perceptions of tangible quality (p=0.000), reliability (p=0.000), responsiveness (p=0.000), assurance (p=0.000), and attention (p=0.000) at Tanjung Balai Hospital to health services during the Covid-19 pandemic. Conclusion: There is a significant relationship between public perception of quality at Tanjung Balai General Hospital for health services during the Covid-19 pandemic.